Intervention in the A conduct pattern: An interdiscipliner model - Gil-Lacruz, Marta (2004)
The type A imples clearly the interaction importance of the psyco, socio and physical variables involves in the behavioral explication. Nowadays the productivity, competitive an constant formation requirements in the laboral environments imply to the employers an strong amount of stress, unhealthy life styles and specif laboral risks. This article analyzes the cientific psychologycial literature about this situation researching the common point of view and their operative consequences in the laboral prevention and health promotion.